2021
DOI: 10.3390/ma14237176
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Mechanical Properties and Residual Stress in Additively Manufactured 316L Specimens

Abstract: In the presented study, LPBF 316L stainless steel tensile specimens were manufactured in three different orientations for the analysis of anisotropy. The first set of specimens was built vertically on the build platform, and two other sets were oriented horizontally perpendicular to each other. Tensile test results show that mean Young’s modulus of vertically built specimens is significantly less then horizontal ones (158.7 GPa versus 198 GPa), as well as yield strength and elongation. A role of residual stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Various materials undergo postcritical deformation: metals [ 15 , 16 , 17 ], rocks [ 18 , 19 ], concretes [ 20 , 21 , 22 ], polymer composites [ 23 , 24 , 25 ], etc. In addition, the softening effect is observed in the in-plane shear response of polymer composites [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various materials undergo postcritical deformation: metals [ 15 , 16 , 17 ], rocks [ 18 , 19 ], concretes [ 20 , 21 , 22 ], polymer composites [ 23 , 24 , 25 ], etc. In addition, the softening effect is observed in the in-plane shear response of polymer composites [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 a) that the microstructure and grains of specimens fabricated in 0° orientation are stretched in the build direction and perpendicular to the compression direction, respectively. This results in anisotropy, with specimens fabricated in 0° orientation having lower tensile strength than those fabricated in 90° orientation [29]. Relative to the same specimen cross-section, the specimens printed in 90° orientation exhibit a more spherical grain structure regarding the x-y-plane.…”
Section: Resultsmentioning
confidence: 99%
“…High RS is one common feature of LPBF parts. [38,39] Such RS is mostly caused by large thermal gradients, which occur during repeated melting and solidification. [40] It is often reported that a large compressive residual stress (RS) is present in the bulk of AM specimens.…”
Section: Discussionmentioning
confidence: 99%